ANALISIS STOCK RETURNS PERUSAHAAN PERBANKAN PADA JAKARTA COMPOSITE INDEX MENGGUNAKAN FAMA-FRENCH THREE-FACTOR MODEL - yolita yolita; Syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2014)
The validity of Fama-French Three-Factor Model has been tested in various stock exchanges to show the explanation power of market risk factor, size risk factor and book-to-market ratio risk factor on excess returns. The purpose of this study is to test the validity of Fama-French Three-Factor Model in banking stocks listed on Jakarta Composite Index. This study also shows the average monthly returns behavior based on the portfolios constructed according to firm size and book-to-market ratio. Three-factor model is empirically compared to one-factor model (CAPM). This study uses multiple linear regression on time-series data in estimating the effects of three variables (market risk factor, size risk factor and book-to-market ratio risk factor) on excess portfolio returns. The data used in this analysis are monthly stock returns, monthly market returns and risk-free rate in the period of February 2008 to January 2014. Average monthly portfolio returns calculated from February 2008 to January 2014 show a positive relation between average return and both firm size and book-to-market ratio. Market risk factor and size risk factor significantly affect the excess returns on four portfolios constructed according to firm size and book-to-market equity ratio. Beside the portfolio including big-size firms with high book-to-market ratio, book-to-market ratio risk significantly affects the excess returns on the other three portfolios. Based on the empirical results, three-factor model works better in explaining the excess portfolio returns than one-factor model.Keywords: Fama-French Three-Factor Model, market risk, size risk, book-to-market ratio risk, stock returns.